Bicuspid aortopathy – molecular involvement of microRNAs and MMP-TIMP. (16th November 2020) - Naito, Shiho; Petersen, Johannes; Sequeira-Gross, Tatiana; Neumann, Niklas; Duque Escobar, Jorge; Zeller, Tanja; Reichenspurner, Hermann; Girdauskas, Evaldas
Abstract: Objectives: We aimed to elucidate the correlation between expression patterns of aortic tissue microRNAs and the aortopathy formation in bicuspid aortic valve (BAV) disease. Methods: All 65 patients who underwent elective aortic valve repair/replacement +/− proximal aortic replacement due to BAV disease with or without concomitant aortic aneurysm were identified from our BAV registry. Aortic tissue was collected intraoperatively from the ascending aorta at the greater and lesser curvature. Aortic tissue microRNAs analysis included 11 microRNAs ( miR-1, miR-17, miR-18a, miR-19a, miR-20a, miR-21, miR-29b, miR-106a, miR-133a, miR-143 and miR-145 ). Furthermore, analysis of MMP2, TIMP1/2 mRNA and the protein expression was subsequently performed. The primary study endpoint was the correlation between microRNAs and MMP2, TIMP1/2 mRNA/protein expression. Results: We found a significant association between miR-133a and TIMP1 mRNA ( r  = 0.870, p  < 0.001), an inverse correlation between miR-143a and MMP2 protein expression ( r = −0.614, p  = 0.044) and a positive correlation between miR-133a and TIMP-2 protein expression ( r  = 0.583, p  = 0.036) at the greater curvature. Conclusion: Our findings indicate that aortic tissue microRNAs may reflect remodelling processes of the proximal aorta in BAV aortopathy. Specific aortic tissue microRNAs may exert their regulatory effects on the aortopathy through their impact on MMPs/TIMPs homeostasis at the level of the greater curvature.